Primary ciliary dyskinesia - Sandra Rovira-Amigo; Mª. Araceli Caballero-Rabasco; Silvia Castillo-Corullón; Noelia Baz-Redón (Barcelona Respiratory Network Reviews)
Primary ciliary dyskinesia (PCD) is a rare genetic respiratory disease caused by a dysfunction of motile respiratory cilia and is characterized by laterality defects, neonatal respiratory distress, recurrent upper and lower airway tract infections, and infertility or subfertility. Diagnosis requires a combination of different tests, such as nasal nitric oxide measurement, high-speed video microscopy analysis, immunofluorescence, transmission electron microscopy for ultrastructural analysis, and genetic testing. It is an underdiagnosed disease, and prompt diagnosis improves its prognosis. The purpose of this article is to review the current knowledge regarding the clinical aspects, management, diagnosis, and treatment of PCD. The diagnosis of PCD is complex, but early diagnosis is important to improve the prognosis. In the near future, patients may benefit from specific treatments.